A study of homocysteine level at the III trimester of pregnancy - Sharma, Varuni; Shukla, Navin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Homocysteine is an amino acid which has sprung into prominence in the past few decades. Levels of maternal serum homocysteine normally decreases with gestation, either due to a physiological response to the pregnancy, increase in estrogen, haemodilution from increased plasma volume or increased demand for methionine by both the mother and fetus. Methods: A prospective randomized controlled clinical trial of 50 patients was carried out in Kamla Raja Hospital and outpatient Department of Gajra Raja Medical College, Gwalior from October 6th to October 2007, which was further categorized into socio-demographic and clinical factors. Results: Out of 50 patients, it was found that there were 31(62%) cases below the age of 25 years whereas 19(38%) cases were above the age of 25 years, 30(60%) cases were educated below the primary level whereas 20(40%) cases were educated above the primary level, 10(20%) cases belonged to rural areas whereas 40(80%) cases belonged to the urban areas. According to the socio economic distribution, 11(22%) cases were below class II whereas 39(78%) cases were above class II. According to distribution of parity, 22(44%) cases were below primigravida whereas 28(56%) cases were above primigravida. Conclusions: This study concludes that mean of Serum Levels in pregnant women with socio-demographic and clinical factors was statistically insignificant which signifies that age, education, residential areas and hemoglobin are not the factors contributing to the rise in homocysteine level in pregnant women. The diastolic and systolic blood pressure is weakly correlated with serum homocysteine level.